2021
DOI: 10.3390/ijerph18073783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean Platelet Counts in Preterm Infants with and without Retinopathy of Prematurity

Abstract: Platelets are a primary source of pro- and anti-angiogenic cytokines. However, the evidence of their role in retinopathy of prematurity (ROP) is controversial. This retrospective study aimed to compare mean weekly platelet counts between infants with and without ROP over the first 6 weeks of life. A total of 93 infants matched by gestational age and birth weight were recruited (31 with ROP, 62 without ROP). Weekly mean platelet counts and other related risk factors were documented. The repeated measure analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In our study, anemia, thrombocytopenia, blood transfusions, IVH and sepsis were independent risk factors of ROP, especially with progression to severe ROP. This is similar to studies by Pai et al .,[ 23 ] Lim et al .,[ 24 ] Pascal et al .,[ 25 ] and Chang. [ 26 ] All these factors add to the oxidative stress on the immature retina, thereby up regulating VEGF levels, which eventually leads to neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, anemia, thrombocytopenia, blood transfusions, IVH and sepsis were independent risk factors of ROP, especially with progression to severe ROP. This is similar to studies by Pai et al .,[ 23 ] Lim et al .,[ 24 ] Pascal et al .,[ 25 ] and Chang. [ 26 ] All these factors add to the oxidative stress on the immature retina, thereby up regulating VEGF levels, which eventually leads to neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PLTs in ROP is not yet fully understood. PLTs are cytoplasmic clumps without nuclei produced by megakaryocytes and have active physiological properties that regulate neovascularization, fibrin formation and deposition ( 18 , 19 ). Studies ( 19-22 ) have shown that PLTs locally promote or inhibit angiogenesis.…”
Section: Effect Of Hematological Indicators On Ropmentioning
confidence: 99%
“…PLTs are cytoplasmic clumps without nuclei produced by megakaryocytes and have active physiological properties that regulate neovascularization, fibrin formation and deposition ( 18 , 19 ). Studies ( 19-22 ) have shown that PLTs locally promote or inhibit angiogenesis. Platelets contain granules that store regulators of angiogenesis, including VEGF and angiogenesis inhibitors (such as endothelial inhibitors), which are released, thus regulating angiogenesis ( 23 ).…”
Section: Effect Of Hematological Indicators On Ropmentioning
confidence: 99%
“…The search process PRISMA flow diagram is depicted in Figure S1. Of 2645 studies with potential relevance, 21 were included [6,7,9,10,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. These studies reported on 3625 infants.…”
Section: Characteristics Of the Studies And Risk Of Bias Assessmentmentioning
confidence: 99%
“…Bayesian model-averaged meta-analysis (BMA) of the association of severe ROP with platelet counts in phase 1 (A) and phase 2 (B). Hedges' g < 0 indicates lower platelet counts in the ROP group[6,7,[27][28][29][30]35,36,[39][40][41].…”
mentioning
confidence: 99%